Depth perception eaudiobook - Castillo, Linda (Tantor Media, 2018)
A killer is watching . . . Nat Jennings nearly died the night her family was murdered—and spent the next three years wishing she had. Now, she is returning to the sleepy bayou town of Bellerose, Louisiana, driven by cryptic messages only she can hear—messages pleading for her help . . . After serving six years for a crime he didn't commit, Nick Bastille is back in Bellerose, mourning his precious son, who drowned while Nick was away at prison, unable to protect him. But when Nat approaches him with a shocking revelation, his denial slowly turns to a desire for revenge . . . Together, they will hunt for a merciless killer who nearly destroyed them both once before—and is now preparing to finish them off once and for all . . .